Frog Adventure: 2D Based Platformer Game Design with HTML5 - Tawakal, Rayendra; Hezma, Mela; Cahyani, Dewi Regita (Gameology and Multimedia Expert, 2024)
A game is an activity or form of entertainment that involves players in a structured system of rules. Typically, games involve clear goals, challenges, interaction, and decision making by players. Games can be played individually or in groups, either physically or via electronic media such as computers, game consoles, or mobile devices. This report provides in-depth information about the game "Frog Adventure" by choosing Javascript as the main programming language, as well as notepad++ for the code editor container to help create the designed game. The aim of making this game is to fulfill the final assignment in the Game Development course. "Frog Adventure" is a game that combines friendly gameplay, attractive graphics and positive user experience. This information provides a better understanding of the game's strengths and weaknesses, as well as suggestions for future development.